Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Given h(x) = 3x² - 6x +4, find h( - 6).
....
h( - 6) =


Sagot :

Answer:

h(-6) = 3(-6)² - 6(-6) + 4

= 3(36) + 36 + 4

= 148

You basically just substitute x with -6 that's all